Efficient Market of Indonesia Shariah Index during Covid - Faisal, Andri; Soepriyono, Gatot (Jurnal Ekonomi dan Perbankan Syariah, 2024)
ABSTRACT. The capital market is a place to gain capital at there. There is efficient market that past stock price reflects the current recent price. Unfortunately, the stock price is so volatile and it is difficult to predict it. The concept of random walk also occurs in stock price or stock index. During the covid, the stock price decrease and it is so interesting to predict the stock whether follow the random walk or not.  In order to forecast stock price, the investor should know the price of the stock. They can get benefit from the difference of the stock. The adf and KPSS test show the Jakarta shariah index does not follow random walk, meaning the index can be forecast.  The result of the test shows the best model is ARIMA (5,1,2). Arima is a best forecasting method that can predict stock price. The Model has passed Ljung Box, ACF Graphics and also PACF Graphics.